The Destiny of Bulgarians in Republic of Albania after Russo-Turkish Liberation War - Mancheva, Galya (Research Papers, 2019)
The present study aims at tracing the fate of the Bulgarian minority within today’s Republic of Albania during the period between the Russo-Turkish liberation war and the present days. The objective is specified by two main tasks: (1) to draw the historical prerequisites for the settlement of the Bulgarian population on the territory of the present-day Republic of Albania; and (2) to outline the policy of the Republic of Bulgaria regarding the Bulgarian population on the territory of today’s Republic of Albania Russian-Turkish Liberation War to this day.For the achievement of the research tasks, two main periods are conditionally defined: (1) first period - from the first settling of Bulgarians on the present lands of the Republic of Albania to the Russo-Turkish War of Liberation (V-XIX century) and (2) Russo-Turkish War of Liberation to the present (XIX-XXI century). The period up to the Russo-Turkish War of Liberation included a retrospective analysis of the historical prerequisites for settling the Bulgarian population in the lands of the present-day Republic of Albania, with two sub-periods: the period up to the 15th century and the period of the Ottoman Empire. The second, conditionally differentiated main period – after the Russo-Turkish Liberation War, was presented through three sub-periods: the socialist, socialist and post-socialist period. The current status of the Bulgarian-Albanian relations is presented, as well as the prospects for the Bulgarian minority living in the borders of today’s Republic of Albania.